How to recover after sea crossing: the importance of small islands for passerines during spring migration. Issue 3 (4th May 2021) - Ferretti, Andrea; Maggini, Ivan; Fusani, Leonida
Abstract : Every year, billions of migratory birds cover thousands of kilometers between their wintering grounds and their breeding areas. Along their migratory route, birds are often forced to break up their journey into several legs, mainly in correspondence with ecological barriers (e.g. seas and deserts), and stopover in areas where they can sleep and rebuild their energy stores. Stopover is a key migratory stage for many songbirds because strategies adopted at this stage may have direct bearing on the success of migration and, consequently, on the fitness of the individual. Although the restoration of energy reserves is likely the main goal for stopover in many cases, our recent studies suggest that there might be other reasons for stopping over, particularly after long non-stop flights. This seems to be the case of millions of songbirds that land on small coastal islands after crossing large waterbodies, although most of these sites do not provide sufficient refueling opportunities. Here, we aim to provide a new perspective on the role of such small islands by reviewing our recent findings on energy management in migratory songbirds. We are convinced that understanding the role of these islands for migratory birds, as well as how birds manage their energy at these sites, represents an important step toward an optimization of conservation strategies, since setting priorities for protection based on food availability alone may miss critical functions of stopover sites.